Design of cost-efficient and photocatalytically active Zn-based MOFs decorated with Cu2O nanoparticles for CO2 methanation. Issue 73 (23rd August 2019) - Cabrero-Antonino, María; Remiro-Buenamañana, Sonia; Souto, Manuel; García-Valdivia, Antonio A.; Choquesillo-Lazarte, Duane; Navalón, Sergio; Rodríguez-Diéguez, Antonio; Mínguez Espallargas, Guillermo; García, Hermenegildo
Abstract : Here we show for the first time a MOF that is photocatalytically active for light-assisted CO2 methanation under mild conditions (215 °C), which can be further improved with the inclusion of metallic nanoparticles. Abstract : Here we show for the first time a MOF that is photocatalytically active for light-assisted CO2 methanation under mild conditions (215 °C) without the inclusion of metallic nanoparticles or any sacrificial agent. The presence of Cu2 O nanoparticles causes a 50% increase in the photocatalytic activity. This result paves the way for developing efficient and cost-effective materials for CO2 elimination.